HYALURONIC ACID IN THE TREATMENT OF ORTHOPAEDIC INJURIES IN ATHLETES: A NARRATIVE REVIEW OF CURRENT EVIDENCE AND CLINICAL APPLICATIONS - Katarzyna Krzyżanowska; Wiktor Chrzanowski; Marta Korchowiec; Lidia Mądrzak; Łukasz Bialic; Julia Kwiecińska; Władysław Hryniuk; Jacek Sitkiewicz; Alicja Toczyłowska; Mateusz Muras; Bartłomiej Roszkowski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Nowadays, orthopaedic injuries are a common occurrence among athletes as a result of repetitive biomechanical stress and high physical demands. With growing interest in non-surgical and regenerative approaches in sports medicine, hyaluronic acid (HA) has emerged as a promising therapeutic option. This narrative review aims to synthesize current evidence on HA’s biological properties and clinical applications in athletic populations, focusing on its role in treating tendon, ligament, and joint injuries, highlighting both its benefits and limitations, and future directions. Methods: The review is based on articles retrieved from PubMed through July 2025. Studies involving athletic populations were prioritized, with emphasis on cohort studies, randomized controlled trials, systematic reviews, and meta-analyses. Key Findings: HA exerts multiple therapeutic effects, including the modulation of inflammation, enhancement of synovial fluid viscosity, support for chondrocytes, and promotion of tissue regeneration. Moreover, it demonstrates beneficial effects in treating a range of sports-related conditions, including tendinopathies (e.g., Achilles and patellar tendinopathies), acute ligament injuries (e.g., ankle sprains), and early joint degeneration. Nonetheless, inconsistencies in study outcomes, heterogeneity of HA products, concerns about cost-effectiveness, and limited athlete-specific trials present ongoing challenges. Conclusion: HA represents a valuable adjunct in the non-surgical management of orthopedic injuries in athletes. While preliminary findings are promising, more high-quality, athlete-specific research is needed to confirm its long-term efficacy, optimize treatment protocols, and explore its full potential as both a therapeutic and preventive strategy in sports medicine.